Review of the species of Macrodactylus Dejean (Coleoptera: Scarabaeidae: Melolonthinae) from the Central American Nucleus - Arce-Pérez, Roberto; Morón, Miguel Ángel (Zootaxa, 2020)
Twenty species of Macrodactylus Dejean (Coleoptera: Scarabaeidae: Melolonthinae: Macrodactylini) from the Central American nucleus are described and illustrated, including two new species from Guatemala: Macrodactylus eniocanoi new species and Macrodactylus escuintlaensis new species. Macrodactylus hondurensis Arce-Pérez & Morón is recorded for the first time from El Salvador. Diagnoses for 18 species previously recorded in the Central American nucleus are provided. A key to all known species of Macrodactylus of Central American nucleus and distributional maps are included.